(untitled) (European Journal of Pure and Applied Mathematics, 2022)
In this paper a new technique using tensor product is presented which yields an exact solution to Burger’s equation ut + αuux = υuxx which is one of the very few nonlinear partial differential equations that can be solved analytically. Moreover we give an atomic solution for linear partial differential equations with and without variable coefficient terms.